(untitled) (American Journal of Pedagogical and Educational Research, 2025)
This scientific article examines the theoretical and practical aspects of using artificial intelligence (AI) technologies in the biomechanical analysis of football players’ movements. The biomechanical characteristics of key technical actions in football—running, acceleration, stopping, turning, kicking, and jumping—are analyzed based on artificial intelligence methods. In addition, the possibilities of AI technologies in improving technical preparedness, preventing sports injuries, and individualizing the training process of football players are scientifically substantiated. The research findings demonstrate that the implementation of digital technologies in football biomechanics is a crucial factor in achieving high sports performance.